2014
DOI: 10.5185/amlett.2013.6498
|View full text |Cite
|
Sign up to set email alerts
|

Novel biodegradable polymeric flocculants based on cationic polysaccharides  

Abstract: Novel flocculants for wastewater and industrial effluents treatment have been developed in authors' laboratory based on modified polysaccharides. These flocculants have unique characteristics i.e. they are efficient with low dose usage like synthetic flocculants (e.g. polyacrylamide) and controlled biodegradable, shear resistant and inexpensive like polysaccharides. As contaminants have varying ionocity, various kinds of nonionic, anionic and cationic flocculants have been developed in authors' laboratory. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
0
33
0
3
Order By: Relevance
“…The flocculation efficiency of the native gums increased after modifications from 60.76% (ASN) to 96.03% (ASG) and 60.80% (AGN) to 96.38% (AGG) at 10 ppm, with significant increase as the dosage increased. The better flocculation efficacy exhibited by the graft copolymerized Albizia gums (ASG and AGG) compared with their native gums (ASN and AGN) may be due to their higher intrinsic viscosity as evidenced in Table 1 [22,37]. AG gum has better flocculant characteristic in the native and the modified gums compared with AS.…”
Section: Flocculation Efficiency Of the Gumsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flocculation efficiency of the native gums increased after modifications from 60.76% (ASN) to 96.03% (ASG) and 60.80% (AGN) to 96.38% (AGG) at 10 ppm, with significant increase as the dosage increased. The better flocculation efficacy exhibited by the graft copolymerized Albizia gums (ASG and AGG) compared with their native gums (ASN and AGN) may be due to their higher intrinsic viscosity as evidenced in Table 1 [22,37]. AG gum has better flocculant characteristic in the native and the modified gums compared with AS.…”
Section: Flocculation Efficiency Of the Gumsmentioning
confidence: 99%
“…AG gum has better flocculant characteristic in the native and the modified gums compared with AS. Branching and molecular weight of polymer chains determine the effectiveness of flocculants [37]. The floc formation is higher in high-molecular-weight branched polysaccharide backbone with flexible grafted polyacrylamide chains.…”
Section: Flocculation Efficiency Of the Gumsmentioning
confidence: 99%
“…Hence, the interest in acrylamide grafted natural polymer has increased over the years owing to their multi-faceted application in many domains. Singh et al (2000) reported a large number of graft copolymers of acrylamide (AM) with polysaccharides such as guargum, xanthan gum, sodium alginate, carboxylic methyl cellulose and starch using ceric ion/HNO 3 acid as redox initiator. Ceric ammonium nitrate (CAN) induced grafting of AM with psyllium is directed towards understanding the influence of concentrations of AM and CAN in the reaction mixture, on percentage grafting by preparing different samples (Mishra et al 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the optimum level, the grafted chains lose their flexibility and behave like a rigid rod. The flocculation efficiency of the above graft copolymers is found to be much higher than that of commercial polyacrylamide-based flocculants because of their greater degree of branching and higher molecular weight [10][11][12][13]. …”
mentioning
confidence: 99%